العمليات الإسنادية في الاستعارة الصوفية: الاستعارة عند النفري أنموذجا - مولى، فريدة (جامعة مولود معمري تيزي وزو - مخبر الممارسات اللغوية, 2021)
إن أكثر ما يلفت الانتباه في خطابات المتصوفة شيوع الاستعارات التي تتولد من الجمع بين عوالم متباعدة، استعارات توحد بين المحسوس والمجرد، المعلوم والمجهول، وتعد الاستعارة التي تقوم على عملية إسناد دوال مجردة إلى دوال محسوسة من أكثر الأنواع شيوعا في خطاباتهم، وبالتحديد في خطاب "النفري"، إذ تتولد الاستعارة" عنده من عمليات إسنادية تجمع بين دوال تنتمي إلى مجالات متباعدة يصعب إدراك التشابه بين الأشياء التي تشير إليها، لأنه يعمد إلى نقل الدوال من حدود دلالاتها المعجمية ويعتبرها دوالا في حقول معجمية أخرى في عمليات إسنادية تكشف عن منافرة دلالية وتوتر دلالي لا يزول إلا بتجاوز المعنى الحرفي إلى المعنى المجازي الذي يوجد بين ضفتيه، هذا ما ستحاول هذه الدراسة أن تجليه من خلال تحليل نماذج استعارية في خطاب النفري.
The most striking thing in the discourses of the Sufis is the prevalence of metaphors that are generated from a combination of distant worlds, metaphors that unite the concrete and the abstract, the known and the unknown. the metaphor, which is based on the process of assigning abstract signs to concrete ones is one of the most common types in their discourses, more particularly in al-Nafir's discourse, as a metaphor is generated from assignment processes that combine signs belonging to divergent domains, thus it is difficult to perceive the similarities between the things they refer to, because it tends to transfer the signs from the limits of their lexical significance and considers them as signs in other lexical fields that reveal semantic dissonance and semantic tension. The latter does not disappear unless the literal meaning goes beyond the metaphorical meaning that exists between its two sides. This is what this study will try to demonstrate through the analysis Al nifari* metaphors models.
Keywords: اللسانيات اللغوية -- الاستعارة الصوفية -- الخطاب العربي -- علم الدلالة